The Downfall of the Rehabilitative Ideal and the Establishing of a New Political Legitimacy in Swedish Crime Policy: 1965 to 1989 - Andersson, Robert (Bergen Journal of Criminal Law & Criminal Justice, 2018)
The downfall of the rehabilitative ideal is considered a decisive episode if we want to understand the changes that have transpired in crime policy the last three to four decades. In Sweden, the downfall followed abruptly on the final establishing of individual prevention as theoretical bases for crime policy by the enactment of a new penal code in 1965. This paper follows the trajectory of the downfall in Sweden by doing a genealogy thereof. The purpose is to contribute to a more empirically developed understanding of the course of Swedish crime policy during the formative years of the 1970s to the early 1990s. Firstly, the paper addresses the topic by examining the scholarly critique that paved the way for the downfall of the rehabilitative ideal. Secondly, the paper analyses the political handling of the downfall and the consequence this had for policy. Methodological this is done by way of genealogy exploring the historical pedigree of present-day crime policy in Sweden, not as a linear development, but as plural and sometimes contradictory pasts. Theoretical the paper aims to analyze the trajectory by way of a governmentality perspective, i.e. it focuses on crime policy as a means of governing life and the population, thus exploring the different forms governing takes.